One Earth, one People : The Mythopoeic Fantasy Series of Ursula K. Le Guin, Lloyd Alexander, Madeleine L'Engle and Orson Scott Card - Oziewicz, Marek (Jefferson, N.C. : McFarland & Co, 2008)
"Presents the genre from a holistic perspective, arguing that this subgenre of fantasy literature is misunderstood as result of decades of incomplete and reductionist literary studies. Asserts mythopoeic fantasy is the most complete literary expression of a worldview based on the existence of supernatural powers and could transform social consciousness with renewed emphasis on anticipating the future"--Provided by publisher.
The confusion over fantasy and the confusions of the theoretical era -- Reductionist and holistic criticisms in a battle of worldviews -- Mythopoeic fantasy as a modern genre -- Twentieth-century rehabilitation of myth and the search for a new story -- Rediscovering harmony : Ursula K. Le Guin's Earthsea sequence (1964-2001) -- Bridging the past with the future : Lloyd Alexander's Prydain chronicles (1964-1973) -- Integrating science and spirituality : Madeleine L'Engle's Time quartet (1962-1986) -- Reconnecting with nature : Orson Scott Card's Tales of Alvin Maker (1987-2003).
Includes bibliographical references (p. 245-258) and index.
Keywords: Fantasy fiction, American -- History and criticism; Children's stories, American -- History and criticism; Le Guin, Ursula K., -- 1929-2018.; Alexander, Lloyd; Card, Orson Scott; L'Engle, Madeleine -- Criticism and interpretation; Myth in literature